Assessment of the Population Structure and Regeneration Status of Different Communities of Vachellia gerrardii in Al-Haski Valley, Al-Taysia Reserve, Kingdom of Saudi Arabia - Bali, Maher Mohammad; Al-Dughairi, Ahmed Abdullah; Al-Zubaidi, Ali Ebrahem (Journal of agricultural, environmental and veterinary sciences, 2025)
Assessment of population structure provides necessary information about the status and disturbance of the forest key supporting indicator for forest management and conservation interventions.  In this study, current Vachellia gerrardii  community status in Al-Haski Valley in Al-Al-Taysia Reserve was assessed in term of population structure and regeneration pattern. Several sites were also selected for data collection, and the population status of Acacia trees and regeneration patterns were measured. The population structure was then analyzed and classified according to the distribution of tree height classes and crown area size, in order to determine the potential effects of other factors on the populations. We also assessed the status of new regeneration, tree density, tree diameter, height, crown area, canopy cover percentage, associated trees and shrubs, and fluctuations in the Emberger drought index. The study showed that the Hasaki Valley has been suffering from recurrent and variable drought over the past thirty years (1993-2023). This has affected the condition of Acacia trees by reducing tree density and the abundance of natural regeneration per unit area in different valley sectors. It also affected the structure of Acacia populations and tree growth characteristics (diameter, height, and crown area). While the protection of the Hasaki Valley in 2018 contributed to mitigating this damage through the growth of a new generation (young trees) of Acacia trees in the valley, as well as the process of regulating grazing in the various valley sectors.
Keywords: Population structure; Regeneration; Stand density; Size-class distribution